Micro-inflammation Characterized by Disturbed Treg/Teff Balance with Increasing sIL-2R in Patients with Type 2 Diabetes - Cai, B.; Zhang, J.; Zhang, M.; Li, L.; Feng, W.; An, Z.; Wang, L. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Type 2 diabetes mellitus (T2DM) has been gradually considered as a micro- inflammatory disease. To explore the significance of peripheral CD4+ regulatory T cells and CD4+ effector T cells in T2DM, we analyzed inflammation, humoral and cellular immune state in patients with T2DM.118 patients with T2DM without complications and 116 healthy volunteers were included. Serum C-reactive protein (CRP), Complement 3 (C3), Complement 4 (C4), IgG, IgA, IgM, plasma sIL-2 R and peripheral T lymphocyte subsets (including CD4+ CD25high regulatory T cells (Treg) and CD4+ CD25low+median effector T cells (Teff)) were analyzed by rate nephelometry immunoassay, chemiluminescence immunoassay and flow cytometry, respectively.(1) micro-inflammation state in T2DM: Serum CRP, C3, IgA and plasma sIL-2 R were all significantly higher in T2DM than those in healthy control (HC) (all P<0.05). (2) Disturbance of cellular immune in T2DM: Compared with HC, the percentage of peripheral CD3+CD4+T cells and ratio of CD3+CD4+T cells to CD3+CD8+T cells in T2DM were both significantly increased (P<0.05); and the percentage of peripheral CD4+CD25+T cells, Teff cells increased (P>0.05), Treg cells strikingly decreased in T2DM (P<0.05). A positive correlation between sIL-2R levels and peripheral CD4+CD25+T cells or Teff cell percentages, as well as a negative correlation between plasma sIL-2 R levels and serum HDL, LDL or CHOL levels in T2DM were shown (all P <0.05).Micro-inflammation state in T2DM was characterized by increased sIL-2 R, elevated CD3+CD4+T cells and the imbalance of Treg cells and Teff cells, which as one of the pathogeneses took part in inflammation reaction in T2DM.
Keywords: immune imbalance; regulatory T cells; effector T cells